Remembering ecologist Margaret Bryan Davis (1931–2024) - Elizabeth A. Lynch; Randy Calcote; Catherine A. Zabinski; Sara C. Hotchkiss (Proceedings of the National Academy of Sciences, 2025)
Margaret Bryan Davis, a prominent ecologist, died on May 22, 2024. She was a Regents Professor at the University of Minnesota and a member of the National Academy of Sciences. Her students remember her as a creative and clear-thinking scientist who combined the tools and perspectives of paleoecology with ideas and problems of ecology in order to understand long-term forest dynamics. She was a champion of diversity and equity in science.